1999
DOI: 10.1093/mutage/14.5.513
|View full text |Cite
|
Sign up to set email alerts
|

Induction of polyploidy and apoptosis after exposure to high concentrations of the spindle poison nocodazole

Abstract: The proportions of aneuploid/polyploid versus euploid cells formed after treatment with spindle poisons like nocodazole are of course dependent on the relative survival of cells with numerical chromosome aberrations. This work aimed at studying the survival of polyploid cells formed after treatment with a nocodazole concentration sufficient to significantly decrease tubulin polymerization (0.1 microg/ml). First, normal primary lymphocytes were analysed and the following complementary chromosomal parameters wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
25
0
2

Year Published

2001
2001
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(32 citation statements)
references
References 27 publications
5
25
0
2
Order By: Relevance
“…6B, the apoptotic potential of nocodazole was significantly enhanced by STI-571-mediated inhibition of polyploidy. The formation of polyploidy in K562 cells following exposure to nocodazole was described previously by Verdoodt et al (1999). A 10-fold increase in nocodazole (10 M) strengthened the mitotic block induced by nocodazole and minimized mitotic slippage and polyploid formation.…”
Section: Sti-571mentioning
confidence: 55%
See 1 more Smart Citation
“…6B, the apoptotic potential of nocodazole was significantly enhanced by STI-571-mediated inhibition of polyploidy. The formation of polyploidy in K562 cells following exposure to nocodazole was described previously by Verdoodt et al (1999). A 10-fold increase in nocodazole (10 M) strengthened the mitotic block induced by nocodazole and minimized mitotic slippage and polyploid formation.…”
Section: Sti-571mentioning
confidence: 55%
“…As demonstrated with other microtubule-targeting agents (MTAs), we showed that activation of c-Jun NH 2 -terminal kinase (McGee et al, 2002), together with the phosphorylation and inactivation of the antiapoptotic proteins Bcl-2 and Bcl-x L are a prerequisite for PBOX-6-mediated apoptosis (McGhee et al, 2004). In addition, we demonstrate herein that the PBOX compounds induce the formation of polyploid cells, a characteristic shared with other MTAs (Verdoodt et al, 1999). Generally, in response to MTAs, cells enter mitosis, transiently arrest, and exit without undergoing cytokinesis.…”
mentioning
confidence: 51%
“…Delayed mitosis can lead to DNA rereplication and apoptotic death. DNA rereplication caused by delayed mitosis is naturally blocked by p53, while apoptosis is p53 independent (6,74). As DT40 cells do not express p53 (66), TBP-Het cells can undergo DNA rereplication and also exhibit a high proportion of apoptotic cells.…”
Section: Discussionmentioning
confidence: 99%
“…The absence of functional p53 is permissive for the generation/survival of polyploid cells in a number of in vitro systems; HeLa cells proliferating in vitro without any treatment other than antisense p53 (Iotsova and Stehelin, 1995), human leukemia cell lines treated with nocodazole ( (Verdoodt et al, 1999), U87MG glioma cells exposed to 1,3-bis(2choroethyl)-1-nitrosourea (Wu et al, 2001a), Msh2-deficient fibroblasts treated with cisplatin (Strathdee et al, 2001), the 32D murine myeloid cell line manipulated to overexpress c-myc (Yin et al, 1999), murine T cells subjected to mitotic arrest (Baek et al, 2003), or mouse embryonic fibroblasts treated with IC261, an inhibitor of casein kinase-1d and -e (Behrend et al, 2000), or fused with polyethylene glycol (Castedo et al, 2001), just to give a few examples. The overexpression of Aurora-A, Aurora-B and Plk causes cell division defects with consequent multinucleation (mostly tetraploidization) and an increase in centrosome number.…”
Section: P53 and The Polyploidy Checkpointmentioning
confidence: 99%